Pengaruh Ekstrak Daun Lamtoro (Leucaena leucocephala) terhadap Waktu Kematian Cacing Ascaris suum, Goeze In Vitro - Ramadhan, Mira Rizki; Dharmawan, Ruben; Mashuri, Yusuf Ari (Nexus Biomedika, 2014)
Background. Nematodes infection particularly, Ascaris lumbricoidesÂ  is cronic infection that make serious health problems. Leucaena leaf (Leucaena lecocephala) containÂ  leucanin, leucanon, mimosin and tannin that have been known to have athelmintic effect. This study aimed to determine the effect of Leucaena. Leucaena leafÂ  (Leucocaena leucocephala) extract towards death time of Ascaris suum, Goeze In Vitro.. Methods. This study was a laboratory experimental research using the post-test only controlled group design. The subject were adult worms that have length between 10 -20 cm. The sampling technique was used in purposive sampling. The subject was divides into 6 groups, each group consist of 4 worms, replication performed 4 times. Pirantel Pamoat 5mg/ml was used in Positive Control Group (KKP) and NaCl 0,9% was used in Negative Control Group (KKN). While the handling group was given by leucaena leaf extract in various concentration. 5% b/v was given by first handling group (KP1), 10% b/v was given for KP2, 20% b/v was given for KP3, andÂ  30% b/v was given for KP4. Worms immersed every 60 minutes and counted the number of time. Data were analyzed with regression liner and probit analys. Results. The fastest of death time that given by leucaena leaf is KP4 in the amount of 375 minutest, followed by KP3, KP2 dan KP1. While the death time ofÂ  KKP aproximatelyÂ  at 60 minutes dan 3360 minutes on KKN. The result of Pearson correlation test show close relationship between variation of the concentration and the time of death worms with a correlation coefficient 0,778 marked negative. The result of regression liner show significant p < 0.000,Â  r square .605 with regression equation is Y = 2704 â 503,464 X. The result of probit analys LC50 in the amount ofÂ  10,355%, LT50 is counted at 411,178 minutes LT99 is counted at 571,621 minutes.Â  WhileÂ  37,055 minutes is counted for Pirantel Pamoat. Conclution. Based on this study, in can be concluded that theÂ  Leucaena leucocephala leaf extract affect mortality of Ascaris suum in Vitro. The increasing of extract concentration in inversely propotional with the death time of worms. Keywords : Leucaena Leaf extract, death time,Â  anthelminticÂ